EVALUATION OF DOCTORS’ AWARENESS ABOUT SOCIAL PROBLEMS OF THE PATIENTS - S. A. Yudin; O. N. Barkanova; A. S. Borzenko; V. V. Delaryu (Туберкулез и болезни лёгких)
The questionnaire survey in 92 TB doctors and 144 general practitioners from polyclinics and hospitals showed the low awareness of the doctors about social problems of tuberculosis patients, which contributed to insuffcient resolution of those problems in tuberculosis patients.